How to Become a People Magnet 62 Simple Strategies to Build Powerful Relationships and Positively Impact the Lives of Everyone You Get in Touch With - Marc Reklau ([Great Britain] Maklau Publishing Ltd, 2018)
In his book How to Become a People Magnet international bestselling author Marc Reklau reveals the secrets and psychology behind successful relationships with other people. Your success and happiness in life - at home and in business -, to a great extent, depend on how you get along with other people. Are you able to influence and persuade them? Although success can mean something different for each person, there is one common denominator: other people.
Keywords: Poweful relationships